The Impact Of Working Captital Management And Ownership Structure On Profitability: The Moderating Role Of Firm Growth - Elsa Okta Akila; Supaijo; Mia Selvina (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
This study analyzes the effect of working capital management and ownership structure on profitability, and examines company growth as a moderating variable in consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. A quantitative causal-associative design was applied, involving 29 companies and 145 observations. The variables were measured using Working Capital Turnover (WCTO), Institutional Ownership (IO), Return on Assets (ROA), and Growth Assets (GA), with data analyzed using the Common Effects Model and Moderated Regression Analysis (MRA) in EViews 12. The results show that working capital management and ownership structure do not significantly affect profitability. Based on agency theory, this reflects management's preference for conservative policies that do not directly increase profits. Company growth also does not moderate the relationship between working capital or ownership structure and profitability. From a signaling theory perspective, company growth fails to act as a positive signal due to higher risk and uncertainty in fast growing companies. This study concludes that company growth does not strengthen the influence of internal factors on profitability in the consumer goods sector during the post-pandemic recovery. In Islamic economics, company growth is not only financial but also reflects whether business activities are beneficial, halal, and fair.